y = (e^x - e^(-x))/(e^x + e^(-x))
1. (e^x + e^(-x))y = (e^x - e^(-x)) /* I multiplied both sides by the denominator */
2. (e^2x + 1)y = e^2x - 1 /* I multiplied both sides to e^x to eliminate e^(-x) */
At this point I don't know what to do and I'm lost. Any help is much appreciated, thank you
-Evan
1. (e^x + e^(-x))y = (e^x - e^(-x)) /* I multiplied both sides by the denominator */
2. (e^2x + 1)y = e^2x - 1 /* I multiplied both sides to e^x to eliminate e^(-x) */
At this point I don't know what to do and I'm lost. Any help is much appreciated, thank you
-Evan